Ecologies of learning, training and community participation in higher education. Articulating academic knowledge and experiences - Márquez-García, María Jesús; Calvo-León, Piedad (My University, 2021)
We present part of the results of the Innovation Project “Ecologies of learning, training and community participation in higher education. Articulating academic knowledge and experiences” (PIE-193, 2019-2021) that we are developing at the Faculty of Education Sciences of the University of Malaga. The project investigates a training model based on coinvolvement and commitment to educational and social projects that are sustained in the democratic school, social inclusion, coexistence and community.
Keywords: Educación superior; Profesores -- Educación; Investigación educativa; Investigación evaluativa (Programas de acción social); Teacher education; Participatory research; Social transformation; Higher education